1978
DOI: 10.1364/ao.17.003990
|View full text |Cite
|
Sign up to set email alerts
|

Light propagation in graded-index optical fibers

Abstract: An accurate numerical method is described for solving the Helmholtz equation for a general class of optical fibers. The method yields detailed information about the spatial and angular properties of the propagating beam as well as the modal propagation constants for the fiber. The method is applied to a practical graded-index fiber under the assumptions of both coherent and incoherent illumination. A spectral analysis of the calculated field shows that leaky modes are lost and steady-state propagating conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
357
0
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,015 publications
(364 citation statements)
references
References 7 publications
1
357
0
6
Order By: Relevance
“…Thus the refocusing can only held for a certain distance before reaching an unfocused equilibrium state, which, together with the decay of the leaky modes, sets up a steady-state propagation within centimeters [15].…”
Section: Multiplexed Optical Fiber Sensors For Coal Fired Advanced Fomentioning
confidence: 99%
“…Thus the refocusing can only held for a certain distance before reaching an unfocused equilibrium state, which, together with the decay of the leaky modes, sets up a steady-state propagation within centimeters [15].…”
Section: Multiplexed Optical Fiber Sensors For Coal Fired Advanced Fomentioning
confidence: 99%
“…A different approach to the parabolic approximation involves an operator technique proposed by [55], which was used to approximate the Helmholtz equation for wide-angle light propagation in optical fibers. This approach involves splitting (or factoring) the wave equation into two parts, followed by an approximation of the 'operator-root'.…”
Section: Introductionmentioning
confidence: 99%
“…These approximations were implemented within the acoustic split-step computer algorithm of [25] so that the accuracies of all three operator-root approximations could be compared. Their results indicated that the wider angle parabolic equation of [55] was least sensitive to the choice of reference phase and least effected by phase errors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations